INDONESIAN GOVERNMENT POLICY: LEARNING LITERACY AT TEACHER COLLEGE COLUMBIA UNIVERSITY - Meliyanti Meliyanti; Sani Aryanto (Journal of Professional Elementary Education, 2023)
The purpose of this research is to present a comprehensive overview of the Microcredential program TCRWP in an effort to improve teacher literacy competence in Indonesia. The research method used descriptive qualitative with 53 teachers as subjects from PAUD (Pendidikan Anak Usia Dini/Preschool) and SD (Sekolah Dasar/Elementary School) levels from 14 provinces in Indonesia. The results of the study show the government's success in increasing teachers’ literacy competence through implementation of the TCRWP microcredential program with an indicator of test scores > 80. The rationalization for the success of this program consists of (1) An increase in teachers' understanding of the continuum literacy principle conceptually as a representative polarization of literacy learning in the context of Indonesian education; (2) Capacity building in choosing and developing decodable books and their levels; (3) An increase in ability to formulate reading workshop strategy as an innovative strategy in developing more contextual literacy learning.